Uterine mesothelial cysts mimicking ovarian cysts in a primipara patient with a history of Cesarean section: A case report and review of the literature - Yu-Ting Lin; Jia-Huei Tsai; Mu-En Ko; Ching Hsu; Jiun-Yi Sheen; Bor-Ching Sheu; Wen-Chun Chang (Elsevier, 2024)
Objective: We describe a rare case of uterine mesothelial cysts mimicking ovarian cysts in a primipara patient with a history of Cesarean section. Case report: A 39-year-old female patient with history of Cesarean section presented with dysmenorrhea. Sonography revealed that a hypoechoic and anechoic multicystic complex, which was located on the right side of the pelvic cavity, had infiltrated the adjacent posterior wall of the uterus, and it was preoperatively misdiagnosed as ovarian cysts with suspected endometrioma. Laparoscopic surgery revealed multiple cystic lesions filled with clear yellow fluid on the posterior uterine wall instead of the adnexa. Laparoscopic uterine cystectomy was performed, and the patient's recovery was uneventful. Pathohistological and immunohistochemical examinations confirmed the diagnosis of uterine mesothelial cysts. Conclusion: Uterine mesothelial cysts should be considered in the differential diagnosis of pelvic lesions. Increasing the awareness of this rare disease can contribute to improved evaluation, decision-making, and disease management.